Analysis of Suicidal Deaths in Denizli A 10-Years Retrospective Autopsy Study - Demir, Sümeyra; Yazar, Mustafa Eray; Kurtuluş Dereli, Ayşe; Acar, Kemalettin (The Bulletin of Legal Medicine, 2018)
Objective: In this study, it was aimed to examine the characteristics of suicides in demographic way and to investigate whether it forms difference in various aspects mainly the suicide methods chosen in the subsequent years and especially whether there is an increase in the rate of suicide with firearms.Materials and Methods: In this retrospective study, 444 suicide autopsies which were performed Pamukkale University Faculty of Medicine, Forensic Medicine Department between 2007 and 2016 were examined in terms of the changes in parameters such as age, gender, suicide site chosen and suicide method, the distribution of the suicides due to the seasons and years.Results: Seventy-nine-point one percent of the events are male and 20.9% of them are women. The suicides are seen mostly in 19-30 age group. Hanging was seen to be the most chosen suicide method with 52.3% and the use of firearms follows this with 28.4%. It was noted that the method of firearm suicides increased in the subsequent years and this increase rate was found to be higher in young men.Conclusion: It is observed that a significant increase in the suicides depending on firearms. The fact that the adolescents and young adult males form the risky group indicates that it should be careful about the individuals in this group. New regulations related to the possession and conveyance both the shotgun and firearms and the effective struggle with all kinds of unlicensed gun should also be included in the suicide prevention programs and protocols.
Keywords: age; sex; suicide methods; hanging; firearms; autopsy